REPRESENTASI PERJUANGAN HIDUP ANAK DALAM NOVEL RUMAH TANPA JENDELA KARYA ASMA NADIA: KAJIAN SOSIOLOGI SASTRA WELLEK DAN WARREN - Dona Riski; Elsa Mulya Karlina (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to describe the representation of children's life struggles in the novel Rumah Tanpa Jendela by Asma Nadia using the sociology of literature approach proposed by Rene Wellek and Austin Warren. The research focuses on the forms of children's struggles, the factors underlying those struggles, and the relationship between the representation presented in the novel and the social reality of Indonesian society. This research employed a qualitative approach with a library research method. The primary data source was the novel Rumah Tanpa Jendela by Asma Nadia, while the secondary data sources consisted of books, scientific journals, previous studies, and references related to the sociology of literature. Data were collected through reading, note-taking, and documentation techniques. The data analysis consisted of data reduction, data classification, interpretation, data presentation, and conclusion drawing. The results indicate that the main character's struggles are represented through perseverance in obtaining education, helping the family economy, maintaining optimism despite poverty, and striving to achieve a better future. The representation of these struggles reflects the social reality of children from underprivileged families in Indonesia and demonstrates that literary works function not only as imaginative creations but also as reflections of social life.